VITAMIN B12 DEFICIENCY-A MAJOR CAUSE OF MEGALOBLASTIC ANAEMIA IN PATIENTS ATTENDING A TERTIARY CARE HOSPITAL - Iqbal, Saira Perwaiz; Kakepoto, Ghulam Nabi; Iqbal, Saleem Perwaiz (Journal of Ayub Medical College Abbottabad, 2009)
Background: Folate and vitamin B12 deficiencies have been known to cause megaloblastic anaemia. Since the deficiencies of these two vitamins are very common in Pakistani population, it would be imperative to investigate their role in causing megaloblastic anaemia. The objective of this study was to find out the contribution of folate and vitamin B12 deficiencies in causing megaloblastic anaemia in our patient population. Methods: In this retrospective cohort study, clinical records of 220 patients (101 females and 119 males with an age range of 1-80 years) who presented themselves with macrocytic anaemia at the Aga Khan University Hospital were collected. Data pertaining to complete blood count and serum levels of folate and vitamin B12 were analysed. Results: The mean haemoglobin (Hb) level was 6.8±0.2 gm/dl. Sixty-nine percent of the patients had severe anaemia (Hb<8 gm/dl). Mean±SEM values of haemoglobin, serum folate and serum B12 were not significantly different between males and females (Hb 6.4±0.3 gm/dl vs 6.3±0.3 gm/dl; folate 6.9±0.8 Î·g/ml vs 7.8±1 Î·g/ml; B12 259±65 Ïg/ml vs 225±45 Ïg/ml, respectively). Linear regression analysis showed that serum folate was inversely related with the mean corpuscular volume (MCV, p=0.04). Spearman’s correlation analysis indicated an inverse mild association between MCV and serum folate (correlation coefficient= -0.18). Folate deficiency was 43.4%, while vitamin B12 deficiency was 78.5% in these patients. Seventy-one percent of folate-deficient patients had vitamin B12 deficiency as well, while 26.1% of patients with B12 deficiency had a co-occurrence of folate deficiency. Conclusion: Vitamin B12 deficiency appears to be the major factor leading to megaloblastic anaemia in our study population. Inadequate dietary intake, over-cooking of our food and poor absorption might be contributing to high prevalence of vitamin B12 deficiency in this population. Keywords: Cobalamin deficiency, folate deficiency, macrocytic anaemia, megaloblastic anaemia, nutritional anaemia, vitamin B12 deficiency, Pakistan